Internalization of Islamic Values through a Pesantren Semi-Based Learning Model - Hendi Sugianto; Rofiqi; Abdul Rahim Karim; Ayuningtias Yarun (Laskar Karya, 2026)
The internalization of Islamic values remains a persistent challenge in formal Islamic religious education, where limited instructional time and predominantly cognitive pedagogical orientations constrain the holistic formation of students' Islamic character. This study examines how the Pesantren Semi program facilitates the internalization of Islamic values among upper elementary school students while simultaneously preparing them for full residential pesantren life at subsequent educational levels. Employing a qualitative descriptive case study design, data were collected through participatory observation, in-depth interviews with the foundation principal, Islamic religious education teachers, students, and parents, and systematic documentation analysis. The program is compulsory for students in grades four, five, and six, who participate in a structured weekday boarding cycle running from Monday morning through Saturday noon. Six integrated activity components constitute the program: Qur'anic memorization, congregational prayer, classical Islamic text study, character and etiquette habituation, Arabic language instruction, and religious public speaking. Findings reveal that the program effectively cultivates Qur'anic memorization progress, disciplined worship practices, improved Islamic moral conduct, and strengthened intrinsic motivation for religious learning. Internalization was found to proceed through three interconnected pathways: habituation, role modeling, and reflective engagement. Key institutional challenges included limited qualified teaching personnel, student adaptation difficulties, and suboptimal physical facilities. This study contributes a theoretically grounded and empirically substantiated model of transitional Islamic education that is structurally positioned between the formal school and the full residential pesantren.